2006
DOI: 10.1007/s10719-006-5445-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated N-acetyl- D-glucosaminuronic acid glycosides as inhibitors of influenza virus sialidase

Abstract: The threat of pandemic influenza is a significant concern of governments worldwide. There is a very limited and relatively expensive armament to tackle such a pandemic should it occur. This fact provides much impetus to the scientific community for the discovery of new and less expensive anti-influenza drugs. Our longstanding interest in the inhibition of influenza virus sialidase, coupled with the development of simple carbohydrates that mimic an unsaturated derivative of the enzyme's naturally-occurring liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…However, since anti-influenza virus activity could only be observed in ethanol and alkaline extracts (Figure 1), the phenolic content present in the alkaline extract could represent a promising candidate for the active compound [5c, 9a-c]. In addition, Nakano et al mentioned that the alkaline extract of A. linearis contains uronic acid, which was also reported by Mann et al, which is effective in inhibiting influenza sialidase [7,13]. Our present results suggested that the alkaline extract of A. linearis, extracted using the same method as that described by Nakano et al [7], has potent inhibitory effects against the influenza virus at late stages of infection.…”
mentioning
confidence: 93%
“…However, since anti-influenza virus activity could only be observed in ethanol and alkaline extracts (Figure 1), the phenolic content present in the alkaline extract could represent a promising candidate for the active compound [5c, 9a-c]. In addition, Nakano et al mentioned that the alkaline extract of A. linearis contains uronic acid, which was also reported by Mann et al, which is effective in inhibiting influenza sialidase [7,13]. Our present results suggested that the alkaline extract of A. linearis, extracted using the same method as that described by Nakano et al [7], has potent inhibitory effects against the influenza virus at late stages of infection.…”
mentioning
confidence: 93%
“…Various glycals of N-acetylated neuraminic acid 1 (Neu5Ac; Figure 1), such as, for example, 5-acetamido-2,6anhydro-3,5-dideoxy-d-glycero-d-galacto-non-2-enoic acid 2a (Neu5Ac2en, DANA), [1][2][3][4][5] its 5-perfluoroacetylated analogue 2b (FANA), [6] and the 4-deoxy-4-guanidino congeners of DANA (i.e., Zanamivir, 2c) [1][2][3]7] and of FANA (i.e., 2d), [8] are potent inhibitors of sialidases (neuraminidases, NA). Sialidases are important surface glycoproteins of bacterial and viral membranes that play crucial roles in the spreading of infection to new host cells.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Importantly, presumably by virtue of the hydrophobic side-chain binding subsite 2, 4 retains potent inhibition against influenza A viruses harboring the E119 V mutation that confers resistance to OC 2. 10 We are interested in the development of readily accessible uronic acid-based sialidase inhibitors of type 7 (Figure 2), 11,12 2-acetamido-2-deoxy-Δ 4 -β-D-glucuronides which mimic the naturally occurring sialidase inhibitor 5-acetamido-2,6-anhydro-3,5-dideoxy-D-glycero-D-galacto-non-2-enonic acid (Neu5A-c2en 8) but in which the glycerol side-chain of 8 is replaced by an ether (the glycoside of the glucuronide). An advantage of the uronic acid scaffold is its derivation from inexpensive 2-acetamido-2-deoxy-glucose (GlcNAc) compared to N-acetylneuraminic acid and quinic acid used for the syntheses of 1 and 2, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conversion of glucuronide 14 to the 4,5-unsaturated derivative, Δ 4 -β-D-glucuronide 16, was achieved through DBU-mediated β-elimination. 11,12 To obtain the 3-hydroxy glucuronide 17 for further functionalization at C3, chemoselective cleavage of the C3 O-acetate in the presence of the methyl ester was undertaken using sodium methoxide in methanol. The overall yield of key intermediate 17 in 8 steps from GlcNAc 10 was 40%.…”
Section: ■ Introductionmentioning
confidence: 99%